What makes you beautiful : an exploratory review of facial attractiveness - Lim, Jeremy Wen Bin (2017)
Humans instinctively prefer attractive faces. Yet, little is known at the conscious level why this is so. This literature review attempts to present all facets of what makes a face attractive. A preference for attractive faces is rooted in our evolutionary history, where symmetry and averageness, coupled with developed secondary sexual characteristics, defines facial attractiveness. The benefits of both having an attractive face as well as successfully wooing partners who are facially attractive include having abundant resources, good health, and potentially passing on quality genes to one’s progeny. Sexual dimorphism is also briefly discussed and how such characteristics raises interest in opposite sexes. Good personality can be conveyed through attractive faces, and attractive faces tend to elicit positive judgements. Furthermore, attractive faces are also attended to easily, and positive emotions can bolster one’s facial attractiveness. Various regions of the brain, including the prefrontal cortex, amygdala, nucleus accumbens, orbitofrontal cortex and anterior cingulate cortex, are also associated to be activated when viewing attractive faces. Notably, these mechanisms exist due to evolution, but are perhaps outdated considering modern environmental pressures. Furthermore, media influence is prevalent and may influence definitions of attractive faces. It is also cautioned that facial attractiveness studies tend to be reflective of WEIRD populations and not necessarily generalizable. Additionally, the link between personality and attractive faces is weak at best and should be explored. Lastly, this review did not delve deep into facial feature manipulation techniques and perhaps should be explored in future studies.